Effect of Mowing Height and Fertility on Bermudagrass (Cynodon dactylon) Encroachment and Brown Patch Severity in Tall Fescue. (March 2014) - Cutulle, Matthew; Derr, Jeffrey; McCall, David; Nichols, Adam; Horvath, Brandon
Abstract : Tall fescue is a commonly used turfgrass in the temperate and transition zone areas of the United States. During hot, humid summers, tall fescue is under stress and is susceptible to Rhizoctonia solani (brown patch) infection, causing turf thinning, leading to encroachment from weeds, such as bermudagrass. Field trials were established to evaluate the effect of mowing height and fertility programs on disease severity and bermudagrass encroachment in tall fescue. Mowing at 10 cm resulted in less bermudagrass encroachment than did a 6-cm mowing height. Increasing the nitrogen fertilization level from 49 to 171 and 220 kg N ha −1 generally led to more bermudagrass encroachment at the 6-cm, but not the 10-cm, mowing height. Plots receiving 220 kg N ha −1 annually at the 6-cm mowing height had the most brown patch. Turfgrass cover was greatest in plots mowed at 10 cm and receiving 220 kg N ha −1 annually.